2019
DOI: 10.3892/etm.2019.7855
|View full text |Cite
|
Sign up to set email alerts
|

miR‑133b is a potential diagnostic biomarker for Alzheimer's disease and has a neuroprotective role

Abstract: MicroRNAs (miRNAs/miRs) are involved in post-transcriptional gene regulation and aberrant expression of miRNAs has been widely detected in various human diseases. The aim of the present study was to examine the serum levels of miR-133b in patients with Alzheimer's disease (AD), and to explore its diagnostic value and neuroprotective role in AD. Reverse transcription-quantitative PCR was applied to analyze the serum levels of miR-133b in 105 AD patients and 98 healthy controls. A cell model of AD was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“… 5 , 6 Wang et al 7 reported that the expression levels of miR-433 were reduced in AD patients and that this miRNA has the potential to be a therapeutic target through improving Aβ-induced neurotoxicity. Yang et al 8 provided evidence for miR-133b to serve as a diagnostic biomarker of AD and revealed its neuroprotective role, which is exerted through maintenance of neuronal viability. Although increasing numbers of miRNAs have been discovered, their practical applications in the diagnosis of AD are still limited.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Wang et al 7 reported that the expression levels of miR-433 were reduced in AD patients and that this miRNA has the potential to be a therapeutic target through improving Aβ-induced neurotoxicity. Yang et al 8 provided evidence for miR-133b to serve as a diagnostic biomarker of AD and revealed its neuroprotective role, which is exerted through maintenance of neuronal viability. Although increasing numbers of miRNAs have been discovered, their practical applications in the diagnosis of AD are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high levels of miR-133b could contribute to lowering the expression of FAIM in these neurons. However, in Alzheimer’s disease, miR-133b was found to be significantly downregulated after Aβ25-35 treatment ( Yang et al, 2019 ). In a different study, FAIM levels also appear to be reduced in hippocampal samples from AD patients ( Carriba et al, 2015 ), thus suggesting that the miR-133b-FAIM axis would not be relevant in this disease and opens up the question of whether other miRNAs could be responsible for FAIM downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum miR-133b levels in AD patients are positively correlated with the simple intelligence status test score. The area under the ROC curve of miR-133b in the diagnosis of AD was 0.907, with 1.7 as the critical value, with a sensitivity of 90.8% and a specificity of 74.3% ( Yang et al, 2019 ). There was a significant positive correlation between the serum level of miR-193a-3p and the MMSE score in AD patients ( Cao et al, 2020 ).…”
Section: Mirnas Help With the Diagnosis Of Admentioning
confidence: 99%